Taxonomic revision of the Nippostrongylinae (Nematoda, Heligmonellidae) parasites of Muridae from the Australasian region: the genus Odilia Durette-Desset, 1973 - Durette-Desset, Marie-Claude (2015)
The species of the genus Odilia Durette-Desset, 1973 (Heligmonellidae, Nippostrongylinae) are re-distributed among eight genera of which five are new. This classification is mainly based on certain characters of the synlophe not previously taken into account at the supraspecific level. These characters mainly include the presence or absence of a careen, the relative size of the ridges forming the careen, the development and position of ridge 1', the development of the left ridge and right ridge, and the distribution of the largest ridges. Eighteen of the 20 known species are rearranged in the following genera: Odilia sensu stricto Durette-Desset, 1973 with Odilia mackerrasae (Mawson, 1961) as type species, Chisholmia n. gen. with Chisholmia bainae (Beveridge & Durette-Desset, 1992) n. comb. as type species, Equilophos n. gen. with Equilophos polyrhabdote (Mawson, 1961) n. comb. as type species, Hasegawanema n. gen. with Hasegawanema mamasaense (Hasegawa, Miyata & Syafruddin, 1999) n. comb. as type species, Hughjonestrongylus Digiani & Durette-Desset, 2014 with Hughjonestrongylus ennisae (Smales & Heinrich, 2010) as type species, Lesleyella n. gen. with Lesleyella wauensis (Smales, 2010) n. comb. as type and sole species, Parasabanema szalayi Smales & Heinrich, 2010, and Sanduanensis n. gen. with Sanduanensis dividua (Smales, 2010) as type and sole species. Odilia uromyos Mawson, 1961 and Odilia carinatae Smales, 2008 are not included in the new classification. A key to the proposed genera is provided. The new generic arrangement follows a distribution more related to the biogeographical areas than to the host groups.